The greenhouse gas emissions estimates of hydropower reservoirs in Vietnam using G-res Tool: bridging climate change mitigation with sustainability frameworks - Ghosh, Surajit; De Sarkar, K.; Chowdhury, A.; Holmatov, Bunyod; Rajakaruna, Punsisi (International Water Management Institute (IWMI). CGIAR Initiative on Low-Emission Food Systems, 2023)
Quantifying greenhouse gas (GHG) emissions in hydropower reservoirs is linked with national and international sustainability objectives. Deploying scalable and effective cloud-based technologies improves the accessibility, reproducibility, and timeliness of the quantification process. This novel strategy promotes global sustainability in the hydropower industry while making it easier to comply with environmental regulations. It can promote informed decision-making, increase transparency, and expedite the transition to clean energy sources. Considering the use of cloud computing in GHG quantification can support global efforts to mitigate climate change and advance the development of hydropower systems into more sustainable global infrastructure. Earth Observation (EO) data with cloud computing facilities such as Google Earth Engine (GEE) and G-res (an online tool by the International Hydropower Association) can help fill in the missing data gaps and calculate GHG emissions from hydropower reservoirs in Vietnam following IPCC recommendations for estimating GHG emissions. Seven hydropower reservoirs (Ban Ve, Binh Dien, Ho Ham Thuan, Ho Hoa Binh, Ho Song Hinh, Thac Ba and Yali) from different parts of Vietnam were selected as test cases for calculating GHG emissions using the G-res tool. The initial results from the analysis show that the Binh Dien reservoir reports the highest GHG aerial emission rate per year, while the lowest has been observed for the Thac Ba reservoir. Similarly, the highest emission rate has been observed for the Ban Ve reservoir, while the lowest has been recorded for the Thac Ba reservoir. The initial results reported here provide an understanding of GHG emissions from the hydropower reservoirs (test cases) and are needed to be verified with the respective reservoir authorities for actual emissions.